Pembidangan Fikih dan Cakupannya dalam Kajian Hukum Islam Kontemporer - zahra, fany fadhilatuz (Maliki Interdisciplinary Journal, 2026)
Fiqh is one of the fundamental disciplines in Islamic law that governs human relationships with God, with other human beings, and with the environment. The complexity of contemporary issues requires a more systematic understanding of fiqh, making its categorization essential to clarify its scope and areas of study. This article aims to explain the basic concept of fiqh, its major classifications, and the coverage of six essential branches: fiqh al-ibādah, mu‘āmalah, munākahāt, jināyāt, siyāsah, and environmental fiqh within the framework of contemporary Islamic scholarship. This study employs a library research method by analyzing classical and modern literature, including recent MIJ articles and contemporary Islamic law journals. The findings indicate that each branch of fiqh plays a strategic role in achieving public welfare in accordance with the objectives of Islamic law (maqāṣid al-syarī‘ah). Fiqh al-ibādah strengthens spiritual practice, mu‘āmalah ensures economic justice, munākahāt reinforces family stability, jināyāt upholds justice and social order, siyāsah regulates governance, and environmental fiqh promotes ecological balance. Overall, these classifications demonstrate that fiqh remains dynamic, adaptive, and relevant in responding to modern social, economic, political, and environmental challenges.